Comparative Study of Terrazzo Tiles Produced in Koya and Erbil , and its Suitability for ts Suitability for Construction Purposes - Abdullah, Sarmad F.; Saeed, Sarkawt A.; Qadir, Shler S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2015)
Tiles are durable and have a long lifespan. They may be used as a floor finish for both interior and exterior applications. Experimental and field studies were conducted to investigate the parameters and properties of terrazzo tiles from different regions, namely Erbil and Koya being represented by factories (A) and (B) respectively. These parameters and properties are dimensions, water absorption, modulus of rupture and impact resistance. Test results indicate that the dimensions and modulus of rupture for the tiles from both factories (A) and (B) are conformable with Iraqi specifications, but water absorption of terrazzo tiles from factory (B) does not conform with the Iraqi specification and having surface and total absorption values which are 55.1% and 23.8% higher than that for factory (A) tiles, respectively. The results show that terrazzo tiles of factory (A) have an impact resistance value which is 50% higher than that of tiles from factory (B). The field study which includes questionnaire procedure indicates that 63% of the residents agreed that the terrazzo tiles are beautiful as a floor finishing material and at the same time 94% agreed that this material is expensive. This study shows also that only 20% of Koya residents are satisfied with the quality of the production of factory (B), whereas, 90% of Erbil residents are satisfied with the production of factory (A).